IMPLEMENTATION OF ETHNOMATHEMATICS OF TANIMBAR COIL BURNING USING PMRI APPROACH TO CIRCLE MATERIALS - Jakobus Dasmasela; Mesak Ratuanik (JURNAL EDUSCIENCE, 2023)
Implementation of learning is based on effective learning planning so that students can absorb the material being taught. The problem in this study is the use of a realistic mathematical approach based on the local wisdom of burning stones in the Tanimbar community. The purpose of this study was to instill students' thinking concepts in solving the local wisdom problems of the Batu Bakar community in Tanimbar by paying attention to a realistic mathematics learning approach. The type of research used is descriptive qualitative research. Implementation of learning conducted in Class VIII, SMP N 1 Kormomolin. The results of learning in this class can be concluded that (1) students' reasoning abilities are very good in understanding mathematical problems contained in the local wisdom of the Tanimbar community. (2) the use of a realistic mathematics learning approach based on tanimbar local wisdom is very good for use in mathematics.Keywords: Ethnomatematics, PMRI, Batu BakarAbstrakPelaksanaan pembelajaran didasarkan pada perencanaan pembelajaran yang efektif agar siswa dapat menyerap materi yang diajarkan. Permasalahan dalam penelitian ini adalah penggunaan pendekatan matematis realistik berbasis kearifan lokal pembakaran batu pada masyarakat Tanimbar. Tujuan penelitian ini adalah untuk menanamkan konsep berpikir siswa dalam menyelesaikan permasalahan kearifan lokal masyarakat Batu Bakar Tanimbar dengan memperhatikan pendekatan pembelajaran matematika realistik. Jenis penelitian yang digunakan adalah penelitian kualitatif deskriptif. Pelaksanaan pembelajaran dilakukan di Kelas VIII SMP N 1 Kormomolin. Hasil pembelajaran pada kelas ini dapat disimpulkan bahwa (1) kemampuan penalaran siswa sangat baik dalam memahami masalah matematika yang terkandung dalam kearifan lokal masyarakat Tanimbar. (2) penggunaan pendekatan pembelajaran matematika realistik berbasis kearifan lokal tanimbar sangat baik digunakan dalam pembelajaran matematika.Kata Kunci: Etnomatematika, PMRI, Batu Bakar